Comparison between inflammatory profiles during infections with Staphylococcus aureus and Escherichia coli in a murine air pouch model - Silva, Robson Amaro Augusto da; Guerra, Patrícia Araújo; Queiroz, Annie Ferraz; Figueiredo, Tiana Baqueiro; Marques, Lucas Miranda; Lima, Leonardo Luz; Pereira, Italo Sousa; Santos, Denisar Palmito dos (Scientia Plena, 2015)
Staphylococcus aureus along with Escherichia coli is the most common and one of the oldest human symbiotic bacteria. The Gram- positive bacterium, Staphylococcus aureus, is an important human pathogen that causes a wide variety of diseases, ranging from minor skin infections to life-threatening infections, well as some strains the Escherichia coli, a gram-negative bacterium. In this way, the aim of this study was evaluate inflammatory profiles during infections by Staphylococcus aureus and Escherichia coli in a murine air pouch model. Twelve BALB/c mice had a solution of sterile air inoculated into their dorsal region and were divided into three groups. One group of animals was infected with S. aureus, another group with E. coli and a third group received saline. Twenty-four hours after infection, systemic responses were evaluated by leukocyte counts in the blood, air pouch lavage and bone marrow. Samples of skin were evaluated by morphometry. The IFN-γ present in the air pouch lavage, homogenized spleen and bone marrow, was evaluated by ELISA. The results indicate that the group S. aureus promoted higher cell recruitment to the site of inflammation, confirmed by histopathological analysis. The animals infected with E. coli showed difference in the total blood leucocyte cells evaluation. The dosage of IFN-γ for the study groups was larger than the reference given by the control group. In synthesis, S. aureus induced greater local recruitment of leukocytes.